2007
DOI: 10.1111/j.1600-0625.2007.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 inhibits T cell‐dependent skin inflammation and differentiation and function of antigen‐presenting cells

Abstract: Heme oxygenase-1 (HO-1) is increased in psoriatic skin. We asked for the impact of physiological and pharmacological HO-1 induction on skin immunity and the mechanisms involved in HO-1-induced immunomodulation. We found cutaneous HO-1 expression upregulated comparable with suppressors of cytokine signalling (SOCS)1 and SOCS3 in psoriasis and atopic eczema and temporarily increased in murine ovalbumin-induced late phase reaction (LPR) and 2,4-dinitrofluorobenzene (DNFB)-induced contact hypersensitivity (CHS). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 39 publications
(74 reference statements)
7
53
2
1
Order By: Relevance
“…These DCs overexpressing HO-1 also displayed a diminished ability to stimulate allogeneic T cell proliferation (20,21). HO-1 expression in mouse DCs was recently described to modulate the suppressive capacity of CD4 ϩ CD25 ϩ regulatory T cells (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These DCs overexpressing HO-1 also displayed a diminished ability to stimulate allogeneic T cell proliferation (20,21). HO-1 expression in mouse DCs was recently described to modulate the suppressive capacity of CD4 ϩ CD25 ϩ regulatory T cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have also analyzed the effect of HO-1 on DC biology using CoPP (12,21,45), a classical compound to induce HO-1 in many other cell types (46). It has recently been described that DCs treated with CoPP up-regulate HO-1 and Stat-3 and that is the last molecule, the one responsible for the effect of CoPP using mouse DCs, but unfortunately this point was not analyzed using human and rat DCs and therefore it is difficult to conclude definitively (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat brains, Keap1 could down-regulate heme oxygenase-1 (HO-1) gene expression [71]. Listopad et al [72] reported that the inhibition of HO-1 increased pro-inflammatory cytokine IL-2 production in mouse skin. Pro-inflammatory cytokine IL-2 could activate IKKa in NK cells [73].…”
Section: Optimal Dietary Protein Level Attenuated the Inflammatory Rementioning
confidence: 99%
“…Induction of HO-1 in human peripheral blood monocytes inhibits their chemotactic activity (115). MP infiltrating sites of tissue injury robustly express HO-1 (48,97). Further, HO-1 deficiency in vivo leads to chronic inflammation, perturbed distribution and function of the MPS, and exaggerated inflammatory responses in disease models (65,83,90,131).…”
Section: Mp Ho-1 In Tissue Homeostasismentioning
confidence: 99%